Human Resources as An Area of Improving Standardized Management Systems - Marcin OLKIEWICZ (Communications of International Proceedings, 2023)
One of the main determinants of shaping the quality and effectiveness of the organization's activities, using integrated management systems, are human resources. The aim of this work is to show that human resources determine the shaping of quality within an organization and, therefore, are one of the main directions for the improvement of standardized management systems. The attempt was to present that the effectiveness of pro-quality activities was undertaken by the organization, which are in accordance with the strategy, result from the approval and commitment of employees to proposed changes. The results obtained from the experience of 500 organizations operating in the Central Pomeranian region and the literature on the subject confirm the necessity of improving and appreciating human resources as a "motor" for implementing qualitative changes in organizations. The results of the research, among others, indicate the high awareness of employees of the need to take pro-quality actions resulting from the quality improvement process (indicated by over 56% of the surveyed entities), as well as concerns about the effectiveness of the implementation of a standardized management system resulting from ignorance of the standard by the employees (indicated by 53 % of surveyed entities).
Keywords: human resources; quality; management; quality systems; improvement